Public decision making for heritage conservation: A Hong Kong empirical study. (April 2016) - Yung, Esther H.K.; Lai, Lawrence W.C.; Yu, Philip L.H.
Abstract: This study aims to investigate the objective factors that determine heritage conservation decision makings. A probit regression model, fed with land value data obtained by the residual valuation method, was used to evaluate data sets for 155 built heritage sites designated as statutory monuments or administratively graded by the Antiquities and Monument Office in Hong Kong. Five refutable hypotheses were tested. Although a building at a larger site has a higher chance to be designated a graded heritage building than one at a smaller site, the chances of it being designated a grade heritage building were statistically higher for an older building than for a newer one; not lower for sites under zoning for non-private uses and lower for a privately owned building than a government building; and above all higher for a site with higher property value. The results as a whole dispute the presumption of other researchers, who argued that planning decisions in general, or conservation planning decisions in particular, were dominated by a pro-market sentiment in favor of economic benefits. They form a discussion on the relevance of statistical inquiry for heritage conservation. Highlights: Examines the relationship between land use planning factors and designation of heritage buildings. Evaluates whether conservation decisions were dominant by economic benefits. No conclusive evidence for the proposition that high land values hinders the conservation of heritage buildings. Provides a statistical inquiry for heritage conservation.